Keamanan AKun Web dengan Time Based One Time Password - Khair, Ummul; Budiman, Arief; Chiuloto, Kalvin (Universitas Harapan Medan, 2024)
The rapid development of technology with the large number of people using the internet for daily needs makes it easier to interact and search for information more quickly and precisely. So that comfort is also felt by many parties making transactions, but it needs to be taken into account that when you increasingly want comfort, security also really needs to be considered. Because comfort is inversely proportional to security, the more users want comfort, the more users must pay attention to security. Using the internet in everyday life has become commonplace now, so using a password to secure an account has become a necessity. Several sites on the internet that are widely used use security in the form of passwords for accounts. Time-Based One-Time Password (TOTP) is one way to use passwords for web security. By using TOTP, it will be difficult to steal because the password will be sent in real time every time you enter a web page.